Number 29 (March 1994) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1994)
(March 1994) - History of the Southeastern Fishes Council, 1975-1993. By D.G. Cloutman, 5 pp. Our Southeastern Fishes--What have We Lost and What Are We Likely to Lose. By D.A. Etnier, 5 pp. Constitution of the Southeastern Fishes Council, with Amendments (1976-1977). Corrections and Emendations to "Provenance and disposition of fish specimens appearing in color plates of Kuhene and Barbour's book, The American Darters." By C.R. Gilbert and S.J. Walsh, 1 pp.
Keywords: fishes; history; southeastern fishes council